DESIGN AND EXPERIMENTAL EVALUATION OF AN ION ENGINE PROTOTYPE - BOGHIEZ, Darius Ion; BUICAN, George Razvan (“Henri Coandă” Air Force Academy Publishing House, 2025)
Ion propulsion, traditionally utilized to adjust satellite and space station trajectories, also demonstrates significant potential for aeronautical applications. This paper investigates the feasibility of an ionic motor designed to ionize ambient atmospheric air, eliminating the need for gases such as xenon or argon. The motor features a triangular geometry manufactured using 3D printing technology. Preliminary propulsion calculations are provided, focusing on determining the required voltage to achieve target airspeeds that yield sufficient thrust. These studies help to assemble a model that can propel its weight without using fossil fuel, opening up the possibility of giving up kerosene in the future by bringing new forms of propulsion structures simpler and more economical, introducing new possibilities!
The paper presents the design, construction, and experimental testing of an ion engine prototype intended to demonstrate the feasibility of ionic propulsion in atmospheric conditions. The study focuses on electrode geometry, spacing, and power supply requirements to generate thrust through corona discharge and ion acceleration. Experimental results confirm that the prototype can produce measurable thrust without using conventional fuel, highlighting its potential as a silent, clean propulsion technology. Limitations such as high-voltage requirements and structural stability are discussed, with future work aimed at improving efficiency and scalability for UAV applications.
Keywords: Aerospace; Ionic engine; Generative Design; Additive Manufacturing